Disorders of Emotional Communication in Traumatic Brain Injury - Wauters, Lisa; Marquardt, Thomas P. (Seminars in Speech and Language, 2019)
Traumatic brain injury (TBI) leads to a wide array of behavioral and cognitive deficits. Individuals with TBI often demonstrate difficulties with the recognition and expression of emotion communicated through multiple modalities including facial expression, vocal prosody, and linguistic content. Deficits in emotional communication contribute to a pattern of social pragmatic communication problems, leading to decreased psychosocial function. Growing evidence supports intervention targeting affective processing. This article summarizes the current evidence for evaluation and treatment of affective processing disorders in TBI.
Keywords: Traumatic brain injury; cognitive rehabilitation; emotional processing; affective processing disorders